Utilization of Household Waste to Produce the Fungus Aspergillus niger as Biopesticide and Biological Fertilizer in the Jaya Mulia Farmer Women Group: Pemanfaatan limbah rumah tangga untuk produksi cendawan Aspergillus niger sebagai Biopestisida dan pupuk hayati di Kelompok Wanita Tani Jaya Mulia - Iqbal Erdiansyah; Eliyatiningsih; Mochamad Syarief; Christa Dyah Utami; Berlina Yudha Pratiwi; Fitriyatul Hanifiyah (KHD Production, 2023)
The Jaya Mulia Farmer Women's Group (KWT) is a group of women farmers in Krajan, Suren, Ledokombo, Jember, East Java. KWT Jaya Mulia has problems in producing the Aspergillus niger fungus, namely the availability of the F0 generation A. niger fungus, which still buys long-livers to obtain it at a high price. The high price of F0 generation seeds is caused by the expensive materials used, so another alternative is needed to replace the F0 generation seeds of the fungus A. niger to reduce prices. Producing the biological agent A. niger is a very prospective business, so the introduction of A. niger cultivation techniques need to add to the knowledge and skills of women farmer groups to produce biological agents independently. Based on the situation above, the community service activities to help provide training on cultivation techniques and the production of biological agents in the Jaya Mulia farmer women's group are considered relevant to do. The method used in carrying out community service activities is a participatory community empowerment method that emphasizes community involvement in all activities carried out. This community service activity is planned in four stages of activity, namely stage socialization or counseling, skills training stage, evaluation stage, and mentoring. The activity was attended by 25 members of the Jaya Mulia Farmer Women's Group. Based on the results of the activities that have been carried out, it is known that community service activities can increase the knowledge, skills, and income of farmers in carrying out agricultural cultivation.